2022
DOI: 10.1002/1348-9585.12360
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and social support as key contributors to burnout among Canadians workers in the third wave of the COVID-19 pandemic: A cross-sectional study

Abstract: Objective COVID‐19 has dramatically affected Western Society's relationship with work and contributed to increased worker burnout. Existing studies on burnout have mostly emphasized workplace culture, leadership, and employee engagement as key contributors to burnout. In this cross‐sectional study, we examine the associations between Malach‐Pines Short Burnout Measure (MPSBM) scores and participant's self reported personal characteristics, financial strain, workplace conditions, work‐life balance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(73 reference statements)
1
2
0
Order By: Relevance
“…In situations where social exchange is restricted, as was evident during the pandemic lockdown, feelings of loneliness may be exacerbated. This assumption is supported by previous empirical work, which shows positive associations between loneliness and burnout (Card et al, 2022;Wood et al, 2023) as well as with both core elements of burnout, emotional exhaustion (Becker et al, 2022) and disengagement from work (Mohapatra et al, 2023). Although severely understudied, some studies have also reported positive associations between workload/job demands and loneliness (Kallioniemi et al, 2022;Lowman et al, 2023;Walz et al, 2023), as well as technostress and loneliness (Taser et al, 2022).…”
Section: Theoretical Framework and Hypothesessupporting
confidence: 62%
“…In situations where social exchange is restricted, as was evident during the pandemic lockdown, feelings of loneliness may be exacerbated. This assumption is supported by previous empirical work, which shows positive associations between loneliness and burnout (Card et al, 2022;Wood et al, 2023) as well as with both core elements of burnout, emotional exhaustion (Becker et al, 2022) and disengagement from work (Mohapatra et al, 2023). Although severely understudied, some studies have also reported positive associations between workload/job demands and loneliness (Kallioniemi et al, 2022;Lowman et al, 2023;Walz et al, 2023), as well as technostress and loneliness (Taser et al, 2022).…”
Section: Theoretical Framework and Hypothesessupporting
confidence: 62%
“…W orkplace culture and communications play a pivotal role in maintaining the mental well-being of employees. 1,2 Discriminations such as insults, unfair treatment at work, or job denial stemming from race, religion, or language are associated with mental health problems in ethnic minority workers. 3 Because of the chronic labor shortage, Japan has accepted and will recruit more workers from abroad.…”
Section: Workplace Culture and Mental Health Of Ethnic Minority Worke...mentioning
confidence: 99%
“…The pandemic impacted several aspects of our daily lives, and drastically changed how we engaged with each other. The period of the pandemic gave rise to a drastic increase in people’s levels of stress, anxiety and loneliness ( Card et al, 2022 ), forcing governments to address rising public health issues related to mental health ( Cost et al, 2022 ). The pandemic also impacted how we engaged in music practice.…”
Section: Introductionmentioning
confidence: 99%